Modeling, simulation and performance analysis of parabolic trough solar collectors: A comprehensive review. (1st September 2018) - Yılmaz, İbrahim Halil and Mwesigye, Aggrey
Highlights: Current and past studies on modeling of parabolic trough collector are presented. Optical and thermal models and the modeling approaches are discussed in detail. Analytic and ray-tracing approaches are investigated for optical modeling. Steady and transient heat transfer conditions are examined for thermal modeling. Novel, passive and nanofluid techniques are outlined in performance enhancement. Abstract: Solar thermal systems are advantageous since it is easier to store heat than electricity on a large scale. As such, concentrated solar power is receiving considerable interest among researchers, developers and governments. Several concentrated solar power technologies have been developed including the solar tower, the parabolic trough technology, solar dish and linear Fresnel systems. Among them, the parabolic trough solar collector is a proven technology used dominantly for both industrial process heat and power generation. This technology has matured over the years, and its advancement has become the topic of numerous research studies which were the counter driving force of the field. Particularly in recent years, a significant amount of theoretical and numerical studies have been conducted to assess and improve the performance of parabolic trough solar collectors. This review methodologically holds colossal knowledge of current and past studies to assess the optical and thermal performances of parabolic trough solar collectors, modeling approaches and the potential improvements proposed on behalf of the parabolic trough solar collector design. The optical modeling approaches are identified to be analytical and ray-tracing. The review of thermal modeling approaches presents the steady and transient heat transfer analyses of single and two-phase (with direct steam generation) flows. Also, the computational fluid dynamics models used to analyze the physics of parabolic trough solar collectors with a better insight are reviewed and presented. Finally, the studies conducted on the performance improvement of parabolic trough solar collectors are separately examined and presented, these include novel designs, passive heat transfer enhancement, and nanoparticle laden flows.